Influence of funding on advances in librarianship - Nitecki, Danuta A.; Abels, Eileen G. (Emerald, 2008)
Throughout this volume, the influence of research funding on advances in libraries and librarianship is addressed from two perspectives: funding agents and specific initiatives. A collection of chapters concentrate on a number of questions: Do the agendas of those agencies and foundations that fund research in the profession shape the topics of sponsored inquiry and methodologies used to gather evidence for research that advances libraries and librarianship? What are the trends in the questions funded, in the areas of librarianship supported, and perhaps of greatest interest, in the impact funders have made on our understanding of libraries, librarianship, and solving problems that face them? The traditions of 'Advances in Librarianship' offer an appropriate forum to explore these questions through a collection of in depth reviews of the literature and practice.
Includes index.
Keywords: Library science.; Information science.; elektronické knihy; electronic books